Contraceptive Characteristics of Women Living with HIV in the Kumasi Metropolis, Ghana - Akosua A. Gyimah, MB ChB; Emmanuel K. Nakua, MSc; Ellis Owusu-Dabo, PhD; Easmon Otupiri, PhD (Global Health and Education Projects, Inc., 2015)
Objectives: Contraceptive use among women living with HIV is important to prevent the transmission of the infection to their partners, prevent unintended pregnancies and prevent the mother-to-child transmission of the infection. The study sought to determine the contraceptive characteristics of women living with HIV in the Kumasi metropolis. Methods: A cross-sectional study was conducted from July to August 2012 at two HIV/AIDS clinics in the Kumasi Metropolis in the Ashanti Region, Ghana. Interviewer- administered questionnaires were used to collect data from two hundred and ninety five women. Data from one hundred and eighty three women living with HIV and who were sexually active were analsed. Factors associated with contraceptive use were examined using logistic regression. Results: The overall contraceptive use was high; 84.7% were using a modern contraceptive method. The male condom was the commonest contraceptive method (77.0%) used and this was the main contraceptive method promoted at the HIV/AIDS clinic. Dual method usage was low (4.4%). Multivariate analysis showed that the significant predictor of contraceptive use was HIV status disclosure to partner (AOR 0.25; 95% CI = 0.07-0.87;p = 0.03). Conclusion and Public Health Implications: The integration of family planning and HIV/AIDS services could stress dual method use and encourage HIV status disclosure to partner. Key words: Contraceptives • Condom • Women Living with HIV/AIDS • Ghana Copyright © 2013 Gyimah et al. This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.